Illusions of control, underestimations, and accuracy A control heuristic explanation. [article]. - Thompson, Suzanne C.
The illusions of control area is reviewed, and 5 conditions that influence control judgments are identified: skill-related factors, success or failure emphasis, need for the outcome, mood, and the intrusion of reality. It is proposed that individuals use a control heuristic that includes perceptions of intentionality and connection. Judgments of intentionality are based on foreseeability, ability to produce the effect, and valence of the outcome. Judgments of connection are based on the perceived association between the action and the outcome, which includes temporal, shared meaning, and predictive association. Effects of motives to overestimate, underestimate, and have accurate assessments of control are explained, using the concepts of hindsight bias, connection, and counterfactuals. In addition, the relation between the control heuristic and illusory correlation research and applications of the control heuristic to coping with chronic illness are explored. -- (from the author)